A decoupled source current reconstruction method for noisy and reactive near‐field to far‐field transformation. Issue 1 (10th August 2017) - Bod, Mohammad; Sarraf‐Shirazi, Reza; Moradi, Gholamreza; Kiaee, Ali; Jafargholi, Amir; Mousavi, Pedram
Abstract: In this article, a decoupled source current reconstruction method (SRM) for noisy and reactive near‐field (NF) to far‐field (FF) transformation is introduced. It is shown that the traditional SRM for NF/FF transformation shows instability in the regions that the amounts of noise or reactive radiations are noticeable. Therefore, in these regions, equivalent currents should be determined from a Tikhonov SRM equation. However, this equation increases the computational cost of the SRM. To simplify the Tikhonov SRM equation, a Tikhonov radial field retrieval algorithm is also proposed. In this algorithm, the Tikhonov integral equation is decoupled by considering and retrieving the radial components of the electric field. Results of far‐field calculation with both the proposed Tikhonov SRM equation and Tikhonov radial field retrieval algorithm with three different antennas are presented and compared with those of the full‐wave simulation and measurements. The results show more accurate field transformation with the proposed algorithms.